TERRORISM VIOLENCE: ASSESSING THE IMPACT OF EDUCATION PROGRAMS THROUGH MASS MEDIA ON THE ADOPTION OF SECURITY MEASURES IN BURKINA FASO - Ouoba, Marie Madeleine; Lompo, Emmanuel (UI Scholars Hub, 2022)
This paper investigates the impact of mass media education programs (MEP) on the adoption of security measures in the context of terrorism in Burkina Faso. We collected information using questionnaires and key informant interviews in Ouagadougou, Burkina Faso. The results suggest that individuals who were educated on terrorism through MEP display higher intentions to adopt security measures and tend to have positive attitudes toward the role of media in fighting terrorism violence.